2018
DOI: 10.1038/s41598-018-19701-7
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase and Acetylcholinesterase polymorphisms in Multiple Sclerosis patients: implication in peripheral inflammation

Abstract: Multiple Sclerosis (MS) is an autoimmune disease, having not fully understood aetiology, and both genetic and environmental factors contribute to the pathogenesis of the disease. The cholinergic system has been indicated as a mediator of neuro-immune interactions, as well as an internal regulator of immune responses. The aim of the present research was to assess the associations between BChE and AChE genetic variations and serum cholinergic and inflammatory profiles in 102 Relapsing Remitting-MS patients and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 44 publications
4
33
0
Order By: Relevance
“…ACh and its muscarinic and nicotinic receptors are involved in the modulation of inflammation (Di Bari, Di Pinto, Reale, Mengod, & Tata, ). Our previous studies showed that ACh levels and the activity of its hydrolyzing enzymes were altered in MS patients, confirming that ACh may contribute to the dysregulated immune response and inflammation characterizing MS (Di Bari et al., , ; Reale et al., , ). Several evidences indicate that the use of inhibitors of ACh hydrolyzing enzymes is able to ameliorate clinical symptoms in EAE mice, suggesting that a dysregulated homeostasis of the ACh levels may also occur in the CNS of this MS animal model.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…ACh and its muscarinic and nicotinic receptors are involved in the modulation of inflammation (Di Bari, Di Pinto, Reale, Mengod, & Tata, ). Our previous studies showed that ACh levels and the activity of its hydrolyzing enzymes were altered in MS patients, confirming that ACh may contribute to the dysregulated immune response and inflammation characterizing MS (Di Bari et al., , ; Reale et al., , ). Several evidences indicate that the use of inhibitors of ACh hydrolyzing enzymes is able to ameliorate clinical symptoms in EAE mice, suggesting that a dysregulated homeostasis of the ACh levels may also occur in the CNS of this MS animal model.…”
Section: Discussionsupporting
confidence: 55%
“…Previous data from our group with MS patients (Di Bari et al., ; Reale et al., , , ) allowed us to suggest that the altered immune response could be related to changes in the level of ACh and cholinergic marker expression in blood. It is difficult to assess whether the alterations of the cholinergic circuit are cause or consequence of the altered immune response, but our data suggest that at least in MS patients the reduced levels of ACh may contribute to exacerbate the disease.…”
Section: Discussionmentioning
confidence: 72%
“…For example, serum BChE activity levels are reduced in sterile inflammatory responses to surgery and in response to traumatic injury (Zivkovic, Bender, Brenner, Hofer, & Schmidt, ; Zivkovic et al., ). Moreover, genetic variations in BChE have been associated with autoimmune diseases such as arthritis and multiple sclerosis (Reale et al., ; Shahmohamadnejad et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genetic variations in BChE have been associated with autoimmune diseases such as arthritis and multiple sclerosis (Reale et al, 2018;Shahmohamadnejad et al, 2015).…”
Section: Ta B L E 3 Correlations Between Acetylcholine Levels Esteramentioning
confidence: 99%
“…The pathophysiology of AD is related to the depletion of the acetylcholine (ACh) neurotransmitter [3,4]. Acetylcholinesterase (AChE) and butylcholinesterase (BChE) hydrolyze ACh in the synaptic cleft [5,6], and one of the possible therapeutic strategies for symptomatic treatment entails the use of AChE inhibitors [7,8]. According to the cholinergic hypothesis, AChE inhibitors lead to an increase in the ACh concentration in the brain and improvement of AD patients' cognitive functions [9,10].…”
Section: Introductionmentioning
confidence: 99%